Islamic Personal Finance: A Review using Biblioshiny-R: Islamic Personal Finance: A Review using Biblioshiny-R - Amelia Tri Puspita (SMART Insight, 2022)
One form of financial management is personal financial management, which is the process of planning and managing or controlling the finances of individuals. This need is the highest or top type of need because in principle the higher the ability to manage personal finances, the higher the opportunity for financial freedom to be created. This study aims to determine the development map and research trend of Islamic Personal Finance published by well-known journals in the field of Economics and Islamic finance. The data analyzed were from more than 65 research publications indexed Dimensions. The export data is then processed and analyzed using the R Biblioshiny application program to find out the bibliometric map developmentIslamic Personal Finance. The research results show that there are at least 4 clusters of research lines related to Islamic personal finance. In addition, this topic continues to increase both in terms of number and area of ​​study.